2023
DOI: 10.1002/masy.202200165
|View full text |Cite
|
Sign up to set email alerts
|

Benzoate‐Based Inhibitor Film to Prevent Chloride‐Induced Corrosion: Simulation Study of Efficiency of Dry or Hydrated Film

Giuseppina Raffaini,
Fabio Bolzoni,
Marco Ormellese

Abstract: In the last 30 years, many synthetic organic substances have been proposed as promising inhibitors to prevent chloride‐induced corrosion in reinforced concrete structures. Using molecular mechanics (MM) and molecular dynamics (MD) methods the formation of protective film on steel have been investigated at atomistic level considering different organic inhibitors, comparing the theoretical results with experimental data. In previous work, the interaction between chlorides and both dry and hydrated triethylenetet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…After 250 ps, it is observed that LA and OA molecules are oriented parallel to the Fe (110) plane surface, representing the high ability of these molecules to adsorb on the Fe surface via parallel configuration (Figure 7c). The final configuration after 500 ps (Figure 7d) shows that LA and OA are more attracted to the metal surface and that the biggest change in the adsorption behavior of LA and OA molecules caused by their interaction with the Fe surface is affected by the synergistic action of LA@OA, which helps to enhance the surface coverage and, therefore, strong inter-and intramolecular interactions [37][38][39][40][41].…”
Section: Revealing Nature's Strength: Understanding the Corrosion Inh...mentioning
confidence: 99%
“…After 250 ps, it is observed that LA and OA molecules are oriented parallel to the Fe (110) plane surface, representing the high ability of these molecules to adsorb on the Fe surface via parallel configuration (Figure 7c). The final configuration after 500 ps (Figure 7d) shows that LA and OA are more attracted to the metal surface and that the biggest change in the adsorption behavior of LA and OA molecules caused by their interaction with the Fe surface is affected by the synergistic action of LA@OA, which helps to enhance the surface coverage and, therefore, strong inter-and intramolecular interactions [37][38][39][40][41].…”
Section: Revealing Nature's Strength: Understanding the Corrosion Inh...mentioning
confidence: 99%